2015
DOI: 10.1097/tp.0000000000000901
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety as Risk Factors for Morbidity and Mortality After Organ Transplantation

Abstract: Background Depression and anxiety are common mental health problems in transplant populations. There is mixed evidence concerning whether they increase morbidity and mortality risks post-transplant. If such associations exist, additional risk reduction strategies may be needed. Methods Four bibliographic databases were searched from 1981 through September, 2014 for studies prospectively examining whether depression or anxiety (determined with diagnostic evaluations or standardized symptom scales) affected ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
213
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(229 citation statements)
references
References 113 publications
8
213
0
8
Order By: Relevance
“…As it is found that depressed HTx recipients have a higher risk of mortality, screening for depressive symptoms during follow-up is recommended (69)(70)(71). As an approach to increase mental health, the effect of exercise and HIT has been studied.…”
Section: Mental Health; Anxiety and Depressionmentioning
confidence: 99%
“…As it is found that depressed HTx recipients have a higher risk of mortality, screening for depressive symptoms during follow-up is recommended (69)(70)(71). As an approach to increase mental health, the effect of exercise and HIT has been studied.…”
Section: Mental Health; Anxiety and Depressionmentioning
confidence: 99%
“…Therefore, these studies cannot provide any evidence whether depression and social factors present at time of waitlisting impact transplant outcomes and whether systematic assessment of these patient characteristics should already be part of the pretransplant evaluation. A recent meta‐analysis of heart, liver, kidney, lung, and other solid organ transplant patients found depression in general to be related to adverse posttransplant outcomes 18. However, this meta‐analysis included only 4 (smaller single‐center) studies of HTx patients with a pretransplant assessment of depression, which have reported conflicting findings 19, 20, 21, 22.…”
mentioning
confidence: 99%
“…The depression with anxiety group's means for the BDI-II and STAI instruments were higher than those reported by the Florida Cardiac Cohort Normative Descriptive Measures (14): BDI-II =13.9 (versus 10.58), State Anxiety =40.2 (versus 37.26), and Trait Anxiety =40.6 (versus 34.57), suggesting worse depression and anxiety severity in our patients with both depression and anxiety compared to a broad heart failure group.…”
Section: Resultsmentioning
confidence: 79%
“…The median duration of follow-up of all the papers cited in the meta-analysis was 5.8 years. 14 We did not see a relationship at 5 years. The risk may be much higher during a shorter term, as our study found that at 2-3 years, it diminishes with time.…”
mentioning
confidence: 83%